Pelatihan Redesain Instalasi Listrik Untuk Program Konversi Kompor Gas LPG Ke Kompor Listrik Di Desa Nyurlembang - Nrartha, I Made Ari; Sasongko, Sudi Mariyanto Al; Sultan, Sultan; Ginarsa, I Made; Muljono, Agung Budi; Yadnya, Made Sutha (Universitas Mataram, 2024)
The allocation of LPG gas subsidies has increased, putting a burden on state finances, while surplus electricity production is not being utilized optimally. Electrical energy can replace LPG gas by replacing the gas stove with an electric stove. This conversion requires adequate installation to ensure the safe and secure operation of the electric stove. The implementation of the conversion program must be supported by community readiness regarding standard electrical installations for electric stoves in the form of training. Training activities were carried out in Nyurlembang Village, Narmada, West Lombok, as a community service activity. This activity aims to educate and train the public about repairing and redesigning electrical installations for electric stoves. Training methods include lecture, discussion and practice methods. Before and after the activity, participants are given a written test to determine the success of the training activity. The test results show an average score before and after training of 38.33 and 66.00 for the range 0-100. These results show that the training was quite effective with an increase in participants' theoretical and practical knowledge of 27.67.